Bimacrocyclic Pyridines and 1,8-Naphthyridines: Basicities and Application in Base Catalysis - Liebig, Timo; Lüning, Ulrich (Synthesis, 2014)
Di-α-substituted N-heterocycles such as 2,6-halogenopyridines or 2,7-dichloro-1,8-naphthyridines can be coupled with 2,6-bis(alkenyloxy) substituted areneboronic acids. The resulting tetraenes are then cyclized by ring-closing metathesis to give bimacrocyclic concave pyridines or concave 1,8-naphthyridines. The relative basicity of the concave N-heterocycles was measured and their activity and selectivity was tested in the base-catalyzed addition of alcohols to diphenylketene.
Keywords: macrocycles; boronic acids; molecular recognition; basicity; base catalysis